Sulfated zirconia foams synthesized by integrative route combining surfactants, air bubbles and sol-gel transition applied to heterogeneous catalysis - Alves-Rosa, Marinalva A. [UNESP]; Martins, Leandro [UNESP]; Hammer, Peter [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Royal Society of Chemistry (RSC), 2016)
Sulfated zirconia ceramic foams were produced by the sol-gel process using air-liquid foam and surfactants as dual pore templates. The results showed the presence of high porosity (until 93%) and surface area (105 m2 g-1), and a hierarchical structure of pore sizes in the range of macro (between 10 and 76 μm), and meso-scales (≅6 nm). The hierarchical porous structure and pore wall texturization of ceramic foams produced by this process, besides the presence of strong acid sites, certify these materials as heterogeneous catalysts for dehydration reactions.